P‐213: Late‐News‐Poster: Electroluminescence of Oxide Phosphor in Metal‐Oxide‐Semiconductor Structure. Issue 1 (25th September 2020) - Kang, Taewook; Park, Jehong; Park, Boowon; Lim, Jimin; Kang, Hyunwoo; Jeong, Hyundon; Kim, Jongsu
Abstract : The green Zn2 SiO4 :Mn 2+ phosphor film for electroluminescence (EL) was fabricated through a thermal annealing process of spin coated film on n‐type silicon wafer as a semiconductor electrode. The oxide phosphor was placed in metal‐oxide‐semiconductor (MOS) structure, where indium tin oxide was used as a top transparent electrode. The EL device showed the high‐purity green emission spectrum at 525 nm. Its luminance‐voltage and frequency dependence showed the increasing trend up to 100 V and 1 kHz.